2020
DOI: 10.1021/acs.joc.9b02921
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Entry to the 2-Azatricyclo[4.3.2.04,9]undecane Ring System via Tropone

Abstract: A synthesis of the 2-azatricyclo­[4.3.2.04,9]­undecane ring systema hitherto unreported bridged azatricyclic ring systembeginning from tricarbonyl­(tropone)iron and allylamine was accomplished in three steps: (1) aza-Michael addition of allylamine to tricarbonyl­(tropone)­iron; (2) Boc-protection of the resulting secondary amine; and (3) oxidative demetallation leading to a spontaneous intramolecular Diels–Alder reaction. The effect of a variety of parameters on the intramolecular Diels–Alder reaction was in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…68 The modified reactivities associated with the tro-ponoid core of such complexes have been used to good effect, including, as exemplified in Scheme 6, in the assembly of a range of natural products and natural product frameworks. 69 Thus, the parent complex 71 engages in a hetero-Michael addition with allylamine and protection of the 2°a mine of the product as the corresponding toluenesulfonamide gave adduct 72 in 50% overall yield. Decomplexation of the latter compound using ceric ammonium nitrate (CAN) at 0 °C revealed triene 73 that underwent a spontaneous intramolecular Diels-Alder reaction to deliver heterocycle 74 in good yield.…”
Section: Account Synlettmentioning
confidence: 99%
“…68 The modified reactivities associated with the tro-ponoid core of such complexes have been used to good effect, including, as exemplified in Scheme 6, in the assembly of a range of natural products and natural product frameworks. 69 Thus, the parent complex 71 engages in a hetero-Michael addition with allylamine and protection of the 2°a mine of the product as the corresponding toluenesulfonamide gave adduct 72 in 50% overall yield. Decomplexation of the latter compound using ceric ammonium nitrate (CAN) at 0 °C revealed triene 73 that underwent a spontaneous intramolecular Diels-Alder reaction to deliver heterocycle 74 in good yield.…”
Section: Account Synlettmentioning
confidence: 99%
“…Tricarbonyl(tropone)iron (197), an air stable complex synthesized in one step from tropone, 60 has previously been used as a starting material in total syntheses. 61 Griffith 62 showed that this complex could serve as a building block for the construction of the novel bridged azatricycle 200 (Scheme 38). The uncomplexed double bond of 197 was shown to participate in an aza-Michael reaction with allylamine.…”
Section: Strategies Involving Seven-membered Ring Building Blocksmentioning
confidence: 99%
“…Thus, comparatively few general methods exist for accessing these scaffolds, even though they are found within a number of biologically active alkaloids. We recently demonstrated that the readily available, bench-stable tricarbonyl(tropone)iron complex [4] (1, Scheme 1) could serve as a precursor to the previously unreported 2-azatricyclo[4.3.2.0 4,9 ]undecane ring system [5] (3, Scheme 1). We sought to demonstrate that this iron complex could serve as a common, versatile building block for additional azapolycyclic skeletons.…”
Section: Introductionmentioning
confidence: 99%